Preparation of Ag/TiO2 particle for aerobic benzyl alcohol oxidation - Kim, C.-S.; Kye Sang Yoo (한국공업화학회, 2013)
Ag/TiO2 particle was prepared using various ionic liquids by wet impregnation. The properties of the particles were significantly affected by the composition of ionic liquids. This is mainly attributed to different abilities of an ionic liquid to coordinate with the silver particle, leading to various coagulation of silver particles. The catalytic activity of the prepared samples was examined for the aerobic benzyl alcohol oxidation. Among the particles, Ag/TiO2 prepared with 1-octyl-3-methylimidazolium tetrafluoroborate showed the best catalytic performance.